Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1038/nn.2128
|View full text |Cite
|
Sign up to set email alerts
|

Reward prediction based on stimulus categorization in primate lateral prefrontal cortex

Abstract: To adapt to changeable or unfamiliar environments, it is important that animals develop strategies for goal-directed behaviors that meet the new challenges. We used a sequential paired-association task with asymmetric reward schedule to investigate how prefrontal neurons integrate multiple already-acquired associations to predict reward. Two types of reward-related neurons were observed in the lateral prefrontal cortex: one type predicted reward independent of physical properties of visual stimuli and the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 44 publications
6
84
0
Order By: Relevance
“…Because LPFC is concerned with motivation (Kobayashi et al, 2002;Watanabe and Sakagami, 2007;Pan et al, 2008) and the monkey's motivation was higher in the competitive condition, it may be argued that the competitive activity simply reflects the monkey's enhanced motivational level. However, most of the competitive neurons maintained the differential activity even when we analyzed the data after eliminating the effects of the differential motivational levels on neuronal activity, suggesting that the competitive activity does not simply reflect the monkey's motivational level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because LPFC is concerned with motivation (Kobayashi et al, 2002;Watanabe and Sakagami, 2007;Pan et al, 2008) and the monkey's motivation was higher in the competitive condition, it may be argued that the competitive activity simply reflects the monkey's enhanced motivational level. However, most of the competitive neurons maintained the differential activity even when we analyzed the data after eliminating the effects of the differential motivational levels on neuronal activity, suggesting that the competitive activity does not simply reflect the monkey's motivational level.…”
Section: Discussionmentioning
confidence: 99%
“…We were especially interested in the lateral prefrontal cortex (LPFC), because competition involves both cognitive (such as rules and strategy) and motivational (desire to obtain a reward) components, and the LPFC is known to be involved in the integration of cognitive and motivational information (Kobayashi et al, 2002;Watanabe and Sakagami, 2007;Pan et al, 2008). Furthermore, the LPFC is also involved in the processing of social information (Zink et al, 2008;Fujii et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, it projects to dorsolateral prefrontal and premotor regions, and could, thus, influence behavioral output (51,54). Neurophysiological studies have shown that single lateral prefrontal neurons use reward information to increase spatial discrimination, encode reward-based stimulus category, and integrate reward and response history (64)(65)(66). Together, these findings on expected reward value and risk processing in the lateral prefrontal cortex underline the role of this structure as a key component of the decision system of the brain.…”
Section: Individual Differences In Risk Processingmentioning
confidence: 96%
“…Neurons show corresponding reward differential activity (center, single neuron) from the first trial on (right, population average from 107 neurons), suggesting inference without explicit linking A and B stimuli to reward. [From Pan et al (411). Reprinted with permission from Nature Publishing Group.…”
Section: Non-dopamine Responses During Reward Learningmentioning
confidence: 99%